English for Pharmacy Department Student in a Private University in Indonesia: A Need Analysis - Septian Dwi Cahyo; Azwar Abbas (Universitas Ahmad Dahlan, 2023)
This study analyzes the needs of pharmacy students in a private university for English for Specific Purposes (ESP) in Indonesia. The data were gathered through semi-structural interviews based on determining themes with eight selected students who completed the course, a lecturer of English for specific purposes, and supported by document analysis on the ESP syllabus for the pharmacy department. Data analysis was conducted through interactive data collection, reduction, presentation, and conclusion or verification. The result showed that the pharmacy department wants students to have speaking and academic writing skills using English within limited course meetings in one semester. A variety of teaching strategies have been implemented by the lecturer in a big classroom. However, students’ English mastery varies, with limited learning sources and lacking vocabulary.